PENINGKATAN KEMAMPUAN GURU DALAM MELAKUKAN PENILAIAN RANAH SIKAP MELALUI IN HOUSE TRAINING - Rustini Rahayu (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2019)
The objectives of this study were (1) to apply in-house training among teachers in assessing the attitude aspect, and (2) to improve the teacher ability to conduct an attitude assessment through an in-house training model. This study was a school action research (PTS). The study method conducted in two cycles, carried out at SD N Canden, Bantul Regency at 2017/2018 Academic Year. The data was obtained through observation and documentation. The results of each cycle were analyzed using descriptive approach, and then used as reference for the next action. The teacher's ability with the capable category has reached 80%. The results of this study reveal that trainers ability to implement in-house training in the cycle I was in high category (60%) and has increased to 100% in cycle II. The in-house training model was able to improve the teacher ability to assess the attitude aspect. This was demonstrated by the increase of teacher ability from capable category (50%) in the cycle I to be a very capable (70%) and capable (30%) category in the cycle II. The in-house training may improve the teacher's ability to conduct an assessment of the attitude aspect as well.